Antioxidant Properties and Yield of Wood Ear Mushroom, Auricularia polytricha (Agaricomycetes), Cultivated on Rubberwood Sawdust - Teoh, Hoe Leong; Ahmad, Izzah Shuhailah; Johari, Norjuliza Md Khir; Aminudin, Norhaniza; Abdullah, Noorlidah (Begell House, 2018)
Mushroom cultivation has become an important component of agriculture, providing food and contributing to the global economy. It uses vertical space and addresses issues of food quality, health improvement, and environmental sustainability. Auricularia mushrooms are popular ingredients in traditional Chinese cuisine. The objective of this study was to determine yield and evaluate radical scavenging capacity of A. polytricha cultivated on rubberwood sawdust on a large scale; we measured total phenolic content; DPPH, hydroxyl, superoxide anion, and peroxyl radical scavenging; and reducing power. Cultivation on rubberwood sawdust produces an average of 4 harvests per bag and a biological efficiency of 80-82%. The antioxidant capacity investigations revealed that the ethyl acetate fraction was the most potent radical scavenger in all assays except that for superoxide anions, whereas the aqueous fraction exhibited mild to moderate antioxidant capacity in scavenging the various radicals. Artificial cultivation of A. polytricha on rubberwood sawdust yields many sporophores with potent antioxidant capacity.